466 A SINGLE COURSE OF ANTENATAL BETAMETHASONE INCREASES MATRIX METALLOPRPTEINASE-2 IN MATERNAL BLOOD AND PLACENTA. (1st January 2005) - Gharraee, Z.; Beharry, K. D.; Waltzman, J.; Nageotte, S.; Nageotte, M. P.; Modanlou, H. D.
Abstract : A single course of antenatal betamethasone (B) is administered to women with threatened preterm delivery to advance fetal lung maturation. Lung maturation is associated with increased breakdown and remodeling of the lung basement membrane and extracellular matrix. These processes are regulated by matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) which are present in the fetomaternal membranes of the placenta. We examined the effects of a single course of antenatal B on maternal and placental MMPs and TIMPs. A prospective pilot study of three groups of pregnant patients was conducted. Group I (n=21): women who were antenatally treated with a single course of B, and who delivered ≤36 weeks gestation; Group II (n=7): untreated women who delivered ≤36 weeks (preterm controls); and Group III (n=15): untreated women who delivered ≥38 weeks (term controls). Group I was subdivided into women delivering: a) ≤2 weeks (IA, n=13); and b) ≥2 weeks (IB, n=8) post B treatment. Maternal blood and placental samples were collected at the time of delivery for MMP-2, MMP-9, TIMP-1 and TIMP-2 levels. Placental levels were standardized using total cellular protein levels. Maternal MMP-2 levels (ng/mL) were significantly lower in Group II (14.5±1.2, p≤0.05) than Groups IA (17.9±0.67) IB (18.4±0.6), and III (18.2±0.83). Maternal MMP-9 and TIMP-1 remained unchanged. Maternal TIMP-2 was suppressed in Group IA (38.6±10.0, p≤0.05) and Group II (38.5±4.5, p≤0.05) compared to Group III (83.7±12.3), however, in Group IB, the levels were increased (65.0±7.9, p≤0.01) compared to Groups IA and II. As a result, a higher MMP-2 to TIMP-2 ratio was noted in Group IA (0.54±0.06, p≤0.01) than Groups IB (0.32±0.04) and III (0.33±0.04); and a lower ratio was noted in Group IB (0.32±0.04, p≤0.05) than Group II (0.40±0.04). In the placenta, MMP-2 levels were increased in Group IA (117.3±3.9, p≤0.05) compared to Groups II (100.8±6.0) and III (104.5±3.7). Interestingly, TIMP-1 levels were 10-fold higher in maternal blood than placenta, whereas TIMP-2 levels were 2-fold greater in placenta than maternal blood. Data are mean±SEM. A single course of antenatal B acutely enhances maternal and placental MMP-2 synthesis and maternal MMP-2/TIMP-2 ratio. Increased MMP-2 activity may result in increased collagen breakdown, and suggests a mechanism for B's effect on fetal lung maturation. Decreased MMP-2 by 2 weeks post B treatment reflects abatement of the effects of antenatal B known to occur by 7-10 days.